Keterlibatan Perempuan dalam Kepemimpinan Publik: Studi Kepemimpinan Ketua RT Perempuan di Desa Dendun Kepulauan Riau - Silfia Hanani (Kafa`ah: Journal of Gender Studies, 2017)
The trend of the women participation on public leadership shows its limitation in number, even in the modern time, the comparison on the number is still imbalance for many years. This condition mirrors to the number who participate in politic such as parliamentary. To respond to such kind of condition, people in Indonesia try to apply the affirmative action to push the women in taking their part and fill the blank position as the women representation in the particular aspect. Conversely, the number of the women Dendun Village at Mantang District of Riau Province is quantitatively different. In Fact, the number shows the the trends of improvement as there are many of the who run the local competition for Village Office Administrator like neighborhood leader. This fact reveals that, women have been building their awareness in the case of public leadership and play their role as the decision maker. This representation is important as a mean of the women resurrection in finding their self identity as the inseparable part from the prosperous Community Development with gender fairness.